Atopic children and use of prescribed medication: A comprehensive study in general practice - Pols, David H. J.; Nielen, Mark M. J.; Bohnen, Arthur M.; Korevaar, Joke C.; Bindels, Patrick J. E. (PloS one, 2017)
A comprehensive and representative nationwide general practice database was explored to study associations between atopic disorders and prescribed medication in children. All children aged 0-18 years listed in the NIVEL Primary Care Database in 2014 were selected. Atopic children with atopic eczema, asthma and allergic rhinitis (AR) were matched with controls (not diagnosed with any of these disorders) within the same general practice on age and gender. Logistic regression analyses were performed to study the differences in prescribed medication between both groups by calculating odds ratios (OR); 93 different medication groups were studied. A total of 45,964 children with at least one atopic disorder were identified and matched with controls. Disorder-specific prescriptions seem to reflect evidence-based medicine guidelines for atopic eczema, asthma and AR. However, these disorder-specific prescriptions were also prescribed for children who were not registered as having that specific disorder. For eczema-related medication, about 3.7-8.4% of the children with non-eczematous atopic morbidity received these prescriptions, compared to 1.4-3.5% of the non-atopic children. The same pattern was observed for anti-asthmatics (having non-asthmatic atopic morbidity: 0.8-6.2% vs. controls: 0.3-2.1%) and AR-related medication (having non-AR atopic morbidity: 4.7-12.5% vs. controls: 2.8-3.1%). Also, non-atopic related medication, such as laxatives and antibiotics were more frequently prescribed for atopic children. The present study shows that atopic children received more prescriptions, compared to non-atopic children. Non-atopic controls frequently received specific prescriptions for atopic disorders. This indicates that children with atopic disorders need better monitoring by their GP.